Pantayong Pananaw and the History of Philippine Political Concepts - Guillermo, Ramon (Archīum Ateneo, 2024)
Zeus A. Salazar’s approach in writing the history of political concepts in the Philippines represents one of the most challenging and insightful directions within his complex body of work. However, despite its positive contribution to this area of study, it seems that further advances towards a more productive and empirical direction is hampered by certain unnecessarily restrictive assumptions. This study is a preliminary critique of a significant flaw in his approach which gives priority to the etymological meaning of rootwords as opposed to a more empirically oriented approach based on the study of the “semantic fields” of concepts and the use of quantitative data.